To simplify the expression \( (5\sqrt{2})(3\sqrt{6}) \), we can use the properties of multiplication.
-
First, multiply the constants (5 and 3): \[ 5 \times 3 = 15 \]
-
Next, multiply the square roots: \[ \sqrt{2} \times \sqrt{6} = \sqrt{2 \times 6} = \sqrt{12} \]
-
Now combine the results: \[ (5\sqrt{2})(3\sqrt{6}) = 15\sqrt{12} \]
Now, we can simplify \(\sqrt{12}\): \[ \sqrt{12} = \sqrt{4 \times 3} = \sqrt{4} \times \sqrt{3} = 2\sqrt{3} \]
So, substituting this back, we have: \[ 15\sqrt{12} = 15 \times 2\sqrt{3} = 30\sqrt{3} \]
Therefore, the equivalent expression of \( (5\sqrt{2})(3\sqrt{6}) \) is: \[ 30\sqrt{3} \]
Thus, the correct answer is: D. \( 30\sqrt{3} \).